PROGRESSIVE INTERPRETATION OF THE QUR'AN IN TAFSIR AT-TANWIR: MUHAMMADIYAH'S COLLECTIVE IDENTITY ON ENVIRONMENTAL ISSUES - Tarman, Al Faiz Muhammad Rabbany; Suparmun, Arifah Cahyo Andini; Naska, Isral (QiST: Journal of Quran and Tafseer Studies, 2024)
Tafsir At-Tanwir, the progressive interpretations in it cannot be separated from Muhammadiyah's collective identity. The logical consequence of efforts to understand the interpretations in Tafsir At-Tanwir, directly or indirectly, needs to understand Muhammadiyah's collective identity as a whole. Especially in research focused on environmental issues. This research is a library research using a qualitative approach. The research subject (formal object) is Tafsir At-Tanwir, while the research object (material object) is progressive interpretation that includes environmental discourse as researchers found in Tafsir At-Tanwir. While this research uses a descriptive-analytical type of research, in which it will describe and analyze Tafsir At-Tanwir in which it shows the progressive interpretation of the Qur'an on environmental discourse. This research uses collective identity theory to portray the progressive interpretation in At-Tanwir cannot be separated from Muhammadiyah. These interpretations have critical and creative nuances in responding to environmental problems that exist in contemporary times. Actually, the interpretation of At-Tanwir makes critical efforts towards current actual problems such as illegal logging, environmental pollution, exhaust emissions, which ultimately create global warming. Muhammadiyah's collective identity on environmental issues is divided into three points, namely Muhammadiyah's attitude towards environmental issues based on ideology, the characteristics of Islam Berkemajuan, and Muhammadiyah's attitude.